First-trimester utero-placental (vascular) development and embryonic and fetal growth: The Rotterdam periconception cohort. (May 2021) - Reijnders, I.F.; Mulders, A.G.M.G.J.; Koster, M.P.H.; Kropman, A.T.M.; de Vos, E.S.; Koning, A.H.J.; Willemsen, S.P.; Rousian, M.; Steegers, E.A.P.; Steegers-Theunissen, R.P.M.
Abstract: Introduction: Impaired placental development is a major cause of fetal growth restriction (FGR) and early detection will therefore improve antenatal care and birth outcomes. Here we aim to investigate serial first-trimester ultrasound markers of utero-placental (vascular) development in association with embryonic and fetal growth. Methods: In a prospective cohort, we periconceptionally included 214 pregnant women. Three-dimensional power Doppler ultrasonography at 7, 9 and 11 weeks gestational age (GA) was used to measure placental volumes (PV) and basal plate surface area by Virtual Organ Computer-aided AnaLysis™, and utero-placental vascular volume (uPVV), crown-rump length (CRL) and embryonic volume (EV) by a V-scope volume rendering application. Estimated fetal weight (EFW) was measured by ultrasound at 22 and 32 weeks GA and birth weight percentile (BW) was recorded. Linear mixed models and regression analyses were applied and appropriately adjusted. All analyses were stratified for fetal sex. Results: PV trajectories were positively associated with CRL (βadj = 0.416, 95%CI:0.255; 0.576, p < 0.001), EV (βadj = 0.220, 95%CI:0.058; 0.381, p = 0.008) and EFW (βadj = 0.182, 95%CI:0.012; 0.352, p = 0.037). uPVV trajectories were positively associated with CRL (βadj = 0.203, 95%CI 0.021; 0.384, p = 0.029). In girls, PV trajectories were positively associated with CRL ( p < 0.001), EV ( p = 0.018), EFW ( p = 0.026), and uPVV trajectories were positively associated with BW ( p = 0.040). In boys, positive associations were shown between PV trajectories and CRL ( p = 0.002), and between uPVV trajectories and CRL ( p = 0.046). Discussion: First-trimester utero-placental (vascular) development is associated with embryonic and fetal growth, with fetal sex specific modifications. This underlines the opportunity to monitor first-trimester placental development and supports the associations with embryonic and fetal growth. Highlights: First-trimester PV 1 and uPVV 2 trajectories estimate utero-placental development. PV and uPVV trajectories are positively associated with embryonic and fetal growth. Fetal sex modifies associations between placental development and antenatal growth. First-trimester PV and uPVV more closely reflect early than late fetal growth.